A Horizontal Azimuth Pattern-Reconfigurable Antenna Using Omnidirectional Microstrip Arrays for WLAN Application. (25th February 2019) - Yang, Liang; Lu, Cheng; Li, Xiao; Liu, Leilei; Yin, Xiaoxing
Abstract : A horizontal azimuth pattern-reconfigurable antenna with configurable parasitic element arrays for WLAN applications is proposed in this paper. It consists of a control board, a central series-fed omnidirectional microstrip array, four configurable parasitic elements, a bottom conducting plate, and a top supporting plate. The omnidirectional microstrip array is adopted as an exciter, around which the four same parasitic element arrays are arranged at four corners. The p-i-n diodes as switches are placed between the parasitic element arrays and the conducting plate to control the fifteen radiation patterns of the proposed antenna. The parasitic element arrays are configured as reflectors or directors by switching the p-i-n diodes on or off. The bandwidth achieved ranges from 5.00 GHz to 5.27 GHz. A gain of 8.52 dBi is obtained when the antenna reaches the maximum gain in the H-plane at 5.2 GHz. Good agreements between the simulated and measured results were observed. The proposed parasitic structure which has the same structure with the driven element can enhance the horizontal azimuth gain of the antenna. Only 4 p-i-n diodes are used to produce up to 15 useful beam configurations with a gain range of 4.56-8.52 dBi at the horizontal azimuth.